Available Energy Analysis of New Double-capillary Tube Refrigeration System of Refrigerator-freezer - 何茂刚; 宋新洲; 张颖; 张建涛 (Zhileng xuebao)
A new double - capillary tube refrigeration system for refrigerator - freezers was proposed. A capillary tube was added between the two evaporators in the fresh and frozen food storage chests to raise the evaporation temperature of the fresh food, and reduce the heat exchange temperature difference and the available energy loss. PR equation was adopted to calculate the thermodynamic properties of the refrigerants, and the available energy analysis for the vapor compression refrigeration cycle was programmed to calculate thermodynamic performances of the new and the conventional refrigeration cycle of therefrigerator - freezer. The calculation results show that the available energy efficiency of the conventional refrigeration cycle of the refrigerator - freezer is 21.20% and 20.57%, respectively when the refrigerant is R12 and R134a while that of the double - capillary tube refrigeration cycle of the refrigerator - freezer is 23.97%and 23.44%, respectively. By comparison, the available energy efficiency of the new refrigeration system increases by 13.07% and 13.95%, respectively.